Procurement of Food Baskets at Exorbitantly Higher Rates in Chhattisgarh - CAG of India (CAG of India)
Procurement of food baskets under Chief Minister TB Nutrition Scheme at exorbitantly higher rates from lone ineligible bidder resulted in avoidable extra expenditure of INR 5.04 crore.